15-year-old tobacco and alcohol abstainers in a drier generation: Characteristics and lifestyle factors in a Norwegian cross-sectional sample. Issue 4 (June 2019) - Lund, Ingeborg; Scheffels, Janne
Aims: Norwegian adolescents currently drink and smoke less on average than previous cohorts. Based on cross-sectional survey data, the individual and familial characteristics of 15-year-old non-users and users of alcohol and tobacco were compared to identify correlates to abstinence. Methods: The survey was approved by the Norwegian Social Science Service. The sample consisted of 3107 adolescents from a 2011 school-based survey, of which 848 (27.3%) did not drink alcohol nor use tobacco. Associations with leisure time activities, risk perceptions, parenting style and social factors were analysed by logistic regression. Results: Most of the non-drinkers were also non-users of tobacco. Abstainers (neither alcohol nor tobacco use) tended to have less unorganized and more hobby-related leisure time activities, higher risk perceptions for smoking, and monitoring or emotionally supportive parents. They more rarely reported close relationships with their best friend and were more likely to report lower occurrences of drinking and smoking among friends or siblings. Conclusions: Differences in perceived parenting styles and a lower degree of unorganized leisure in the abstainer group points to monitoring and closer emotional ties between parents and children as important factors in adolescent abstinence. An implication of these results is that promoting hobby-based activities might be a useful strategy for preventing alcohol and tobacco use in young people.